Chinese species of the genus of Agnesiella Dworakowska (Hemiptera: Cicadellidae: Typhlocybini), with four new species and four new records - Yan, Bin; Yang, Mao-Fa (Zootaxa, 2019)
Four new species of Agnesiella Dworakowska are described and illustrated, Agnesiella (Draberiella) digita sp. nov., A. (D.) furca sp. nov., A. (D.) innota sp. nov., A. (D.) sinuata sp. nov.. Four previously described species are recorded from China for the first time, A. (D.) aldera Thapa, 1984, A. (D.) ela Dworakowska, 1977, A. (D.) rita Dworakowska, 1982, A. (D.) roxana Dworakowska, 1982. The females of species A. (D.) aldera, A. (D.) ela and A. (D.) roxana are described for the first time. The couple was collected when they were mating. Based on dissection and observation, the phenomenon was found that male and female had different color patches on habitus (Figs 1–6, 10–15, 28–33, 34–39). A checklist and newly key to known species of Agnesiella are provided for species identification from China.